2018
DOI: 10.1002/jbio.201800162
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessments of skin glycated proteins by fluorescence and Raman techniques in diabetics and nondiabetics

Abstract: Diabetes is a complex metabolic disease and has chronic complications. It has been considered a serious public health problem. The aim of the current study was to evaluate skin glycated proteins through fluorescence and Raman techniques. One hundred subjects were invited to participate in the study. Six volunteers did not attend due to exclusion criteria or a change of mind about participating. Therefore, 94 volunteers were grouped according to age range (20-80 years), health condition (nondiabetic, with insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, this combination needs to be tested in future large clinical trials to prove that multimodal low‐cost portable optical devices may be more accurate than benchtop systems and dermoscopy analysis of trained experts. Furthermore, these low‐cost portable systems may be tested for their ability to analyse other diseases (eg to monitor diabetes 31,32 or kidney failure 60 ) and to detect neoplasia in other body locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this combination needs to be tested in future large clinical trials to prove that multimodal low‐cost portable optical devices may be more accurate than benchtop systems and dermoscopy analysis of trained experts. Furthermore, these low‐cost portable systems may be tested for their ability to analyse other diseases (eg to monitor diabetes 31,32 or kidney failure 60 ) and to detect neoplasia in other body locations.…”
Section: Discussionmentioning
confidence: 99%
“…To cover this urgent need in easy‐to‐use low‐cost RS devices for skin cancer screening, we previously developed a portable RS system with handheld Raman probe 30 . Such compact RS‐based systems were also utilized, for example, to analyse human skin in monitoring diabetes 31,32 . In contrast to in‐laboratory systems 19,29,33 with a high degree of detector cooling (from −60 to −120°C), the proposed device operates only at –15°C that significantly decreases the dimensions, weight and cost of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in the field of noninvasive assessment of AGE accumulation using Raman spectroscopy are of particular interest. In a study conducted by Paolillo et al, Raman and fluorescence techniques were simultaneously used [63]. In this study, the degradation of type I collagen and increased glycation was shown in diabetics and changes in the collagen hydration state was noted for diabetic and chronological aging groups, according to Raman spectroscopy data.…”
Section: Optical Approaches In Diagnosticsmentioning
confidence: 78%
“…Raman spectra of skin[63]. Reproduced with permission of John Wiley and Sons F I G U R E 1 1 Terahertz images of a typical member of the, A, control and, B, diabetic groups.…”
mentioning
confidence: 99%
“…However, diagnostic imaging is not the only means to increase the sensitivity and specificity of the currently applied criteria. Another non-invasive examination method with no significant contraindications is fluorescence spectroscopy, which has been used in medical diagnostics for many years [69].…”
Section: Introductionmentioning
confidence: 99%